Perinatal risk and the cultural ecology of health in Bihar, India. (17th August 2020) - Legare, Cristine H.; Akhauri, Santosh; Chaudhuri, Indrajit; Hashmi, Faiz A.; Johnson, Tracy; Little, Emily E.; Lunkenheimer, Hannah G.; Mandelbaum, Alexandra; Mandlik, Harsh; Mondal, Sudipta; Mor, Nachiket; Saldanha, Neela; et al.
Abstract : The objective of the current study is to examine the cultural ecology of health associated with mitigating perinatal risk in Bihar, India. We describe the occurrences, objectives and explanations of health-related beliefs and behaviours during pregnancy and postpartum using focus group discussions with younger and older mothers. First, we document perceived physical and supernatural threats and the constellation of traditional and biomedical practises including taboos, superstitions and rituals used to mitigate them. Second, we describe the extent to which these practises are explained as risk-preventing versus health-promoting behaviour. Third, we discuss the extent to which these practises are consistent, inconsistent or unrelated to biomedical health practises and describe the extent to which traditional and biomedical health practises compete, conflict and coexist. Finally, we conclude with a discussion of the relationships between traditional and biomedical practises in the context of the cultural ecology of health and reflect on how a comprehensive understanding of perinatal health practises can improve the efficacy of health interventions and improve outcomes. This article is part of the theme issue 'Ritual renaissance: new insights into the most human of behaviours'.